Synthesis of Proposed Structure of Aaptoline B via Transition Metal-Catalyzed Cycloisomerization and Evaluation of Its Neuroprotective Properties in C. Elegans - Soobin Kim; Wooin Yang; Young-Taek Han; Dong-Seok Cha (Applied Sciences, 2021)
A concise synthesis of the proposed structure of aaptoline B, a pyrroloquinoline derived from a marine sponge, was accomplished. A key feature of this synthesis is the versatile transition metal-catalyzed cycloisomerization of N-propargylaniline to construct a quinoline skeleton. However, the spectral data of the synthesized aaptoline B did not agree with those of previous studies. The structure of the synthesized aaptoline B was confirmed using a combined 2D NMR analysis. Furthermore, we assessed the possible neuroprotective potential of aaptoline B using the C. elegans model system. In this study, aaptoline B significantly improved the viability and the morphology of dopaminergic neurons of nematodes under MPP+ exposure conditions. We also found that MPP+-induced motor deficits in nematodes were efficiently restored by aaptoline B treatment. Our findings demonstrate the neuroprotective effects of aaptoline B against MPP+-induced dopaminergic neuronal damage. Further studies are underway to explain its pharmacological mechanism.